Uji Patogenitas Spora Beauveria bassiana Strain Wamena Sebagai Agen Hayati terhadap Hama Penggerek Buah Kopi Hypothenemus hampei - Rosye H.R. Tanjung; Mesak Kamarea; Yan P. Yepese (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
Study on virulence test of Beauveria bassiana strain Wamena spore concentration toward (Hypothenemus hampei Ferr.) has conducted at Laboratorium of Hayati BPTP Dinas Perkebunan Provinsi Papua during February to April 2010. This study aimed to identify the effectiveness of B. bassiana strain Wamena which has potency as agent to control pest on fruit of Coffea sp caused by H. hampei. by dipping fruit of Coffea sp into spore suspension. Complete random design was used in this study. Four concentrations ( 0; 0.01%; 0.02%; 0.03% ; 0.04% and 0.05% of B. bassiana spore and four replicates for each concentration were used. Mortality of H. hampei was observed. Results of this study showed that all concentrations of spore killed imago of Hypothenemus hampei Ferr. The highest mortality reached 85.625% at 0.05% of spore within 10 days. Therefore, it could be concluded that 0.05% of spore as effective concentration to control H. hampei. Key words: Beauveria bassiana strain Wamena, Hypothenemus hampei Ferr., Coffea sp., and spore as effective concentration.